Characterization, Structural Identification and Environmental Applications of Flyash Based Zeolite - S. Sapre, Janhavi; S. Rayalu, Sadhana; U. Meshram, Siddharth; Dubey, Nidhi; Kumar, Pawan; Munshi, K.N. (Asian Journal of Chemistry, 2016)
Relatively pure zeolite-A phases have been synthesized from flyash. The formation of these relatively pure phases having wide ranged environmental application is substantiated by detailed structural identification and characterization of flyash based zeolite-A (FAZ-A) using X-ray diffraction (XRD) method. Absolute crystallinity of zeolite-A sample has been determined along with identification of crystalline and amorphous phases. The X-ray pattern of FAZ-A has been compared with commercial standard zeolite-A procured from Degussa. The as-synthesized FAZ-A has been applied for targeting cationic pollutants, viz., ammonium ion and heavy metals (Pb, Cd, Cu) through cation exchange which shows comparable efficiency with commercial samples.